Differences in coronary vasodilatory capacity and atherosclerosis in endurance athletes using coronary CTA and computational fluid dynamics (CFD): Comparison with a sedentary lifestyle. Issue 130 (September 2020) - Feuchtner, Gudrun M.; Langer, Christian; Senoner, Thomas; Barbieri, Fabian; Beyer, Christoph; Bonaros, Nikolaos; Schachner, Thomas; Friedrich, Guy; Baldauf, Benito; Taylor, Charles A; Klauser, Andrea; Rauch, Stefan; et al.
Highlights: Regular endurance training with a minimum of 1 hour per unit and 3 x week improves vasodilatory capacity and reduces high-risk and mixed non-calcified plaque burden. In practice suggests plan, which may provide relief of angina chest pain due to improved vasodilatory capacity. Coronary CTA with FFRCT may be useful for evaluation of CHD in endurance athletes. Abstract: Background: The aim was to assess the effect of endurance exercise on coronary vasodilatory capacity and atherosclerosis by coronary computed tomography angiography (CTA) and computational fluid dynamic (CFD) modelling. Methods: 100 subjects (age 56.2y±11, 29 females) who underwent coronary CTA were included into this retrospectively matched cohort study. Endurance athletes (≥1 h per unit and ≥3 times per week training) were compared to controls with a sedentary lifestyle, and within subgroups with and without sublingual nitroglycerin preparation. CTA image analysis included coronary stenosis severity (CADRADS), total (segment involvement score = SIS) and mixed plaque burden (G-score), high-risk plaque criteria, the coronary artery calcium score (CACS) and CFD analysis including Fractional Flow Reserve (FFRCT ), myocardial mass (M), total vessel lumen volume (V) and volume-to-mass (V/M) ratio. Results: The prevalence of atherosclerosis by CTA was 65.4 % and >50 % coronary stenosis was found in 17.3 % of athletes. Coronary stenosis severity (CADRADS), total and mixed non-calcified plaque burden (SIS and G-score) were lower in athletes (p = 0.003 and p < 0.001) but not CACS (p = 0.055) and less high-risk plaques were found (p < 0.001). The G-score was correlated with distal FFRCT (p = 0.025). V/M-ratio was different between athletes who received nitroglycerin compared with those who did not (V/M: 21.1 vs. 14.8; p < 0.001), but these differences were not observed in the control subjects. Conclusion: Endurance training improves coronary vasodilatory capacity and reduces high-risk plaque and mixed non-calcifed plaque burden as assessed by coronary CTA angiography. Our study may advocate coronary CTA with FFRCT for evaluation of coronary artery disease in endurance athletes.